"WAZZ Up Doc?" Cost Efficient, User Friendly, Patient Trust Level Based on Convenience and the Use of Hypnotherapy Mobile Apps Method - Imelda Imelda; Dewi Puspaningtyas Faeni; Ratih Puspaningtias Faeni; Rinny Meidiyustiani; Retno Fuji Oktaviani (International Journal of Business Studies, 2020)
Counseling method that uses a breakthrough unconscious forces, called hypnotherapy, is very effective in dealing with psychosomatic history. The reason patients' reluctance to visit specialist counseling and therapy; such a negative stigma, negative social perception, shame somebody to public judgment about mental illness, heavy traffic conditions and geographical distance between patient and psychologist, as well as the affordability of the financial condition of the patient. Effective solutions related to the matter is android based application development "WAZZ Up, Doc?" in the era of Society 5.0. These applications in particular have a very high accessibility and user friendly, convenient for 24/7 accessibility and availability. The contribution of this research was to determine the effect of efficiency in transportation, user friendly, increasing the patient's level of confidence in the psychologist / psychiatrist and high accessibility comfort 24/7 on the use of mobile applications hypnotherapy "WAZZ Up, Doc?". The method used is SEM-PLS with 3600 respondents.